2019
DOI: 10.1016/j.neuropharm.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal fluoxetine has enduring sexually differentiated effects on neurobehavioral outcomes related to social behaviors

Abstract: Selective serotonin reuptake inhibitor medications (SSRIs) are prescribed to up to 10% of pregnant women to treat maternal mood disorders. Exposure to these medications in-utero has raised concerns about altered neurobehavioral outcomes; most recently those related to peer-to-peer social interactions and play. While clinical data show that both perinatal SSRIs (pSSRI) and maternal stress can contribute to social behavioral changes in children, minimal animal work has investigated the effects of pSSRIs in relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 63 publications
(94 reference statements)
0
25
0
Order By: Relevance
“…In terms of social interaction at adulthood, the findings are more controversial. Some studies have indicated that developmental SSRI exposure decreases social interaction in either male offspring [25,27] or female offspring [31], while others found an increase in sniffing behavior towards conspecifics [32,33]. When looking at the motivation for social interaction in particular, the majority found that SSRI exposure negatively affects the motivation to start social contact [26,28,29,34].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of social interaction at adulthood, the findings are more controversial. Some studies have indicated that developmental SSRI exposure decreases social interaction in either male offspring [25,27] or female offspring [31], while others found an increase in sniffing behavior towards conspecifics [32,33]. When looking at the motivation for social interaction in particular, the majority found that SSRI exposure negatively affects the motivation to start social contact [26,28,29,34].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showing a decrease in an offspring's 5-HT levels in response to maternal stress suggest alterations within the prefrontal limbic circuitry. Pregestational and prenatal stress reduced hippocampal neurogenesis and reduced synaptic plasticity (synaptophysin and PSD-95 densities) in the mPFC and hippocampus of adolescent rats [150,151,155,160]. Moreover, prenatal chronic unpredictable stress caused hippocampal structural modifications (decreases in ventral hippocampal sub-region volume together with a decrease in number of neurons; increases in dorsal hippocampal sub-region volume) [153].…”
Section: Prenatal Stress-induced Alterations In Brain Circuits and Bementioning
confidence: 99%
“…Different maternal stress models increased fetal and adult offspring plasma and serum (baseline and stress-induced) corticosterone levels, corticotrophin releasing factor, and the hormone adrenocorticotropic and increased amygdala corticotrophin releasing factor gene expression [148,153,154,158,159]. Furthermore, diminished hippocampal glucocorticoid receptor levels and density were detected [158,160]. Of note, maternal stress-induced fetal changes in serum corticosterone and corticotrophin releasing factor have been suggested to cause the discussed 5-HT-ergic modifications.…”
Section: Prenatal Stress-induced Alterations In Brain Circuits and Bementioning
confidence: 99%
See 2 more Smart Citations